ANALYSIS OF PHASE AND ELEMENT COMPOSITION OF RAW MATERIALS AND SEMICONDUCTORS OF THE CAST IRON AND STEEL PRODUCTION PROCESS USING ANALYTICAL SYSTEM ARL 9900 WORKSTATION - P. S. Chizhov (Литьë и металлургия)
Investigation of two tests of certified samples of campanil and agglomerate with the help of the analytical system ARL 9900 Workstation is carried out.